Towards the description of the phase behavior of electrolyte solutions in slit-like pores. Density functional approach for the restricted primitive model - Pizio, O.; Patrykiejew, A.; Sokołowski, S. (Condensed Matter Physics, 2004)
We develop a density functional approach for the phase behavior of the restricted primitive model for electrolyte solutions confined to slit-like pores. The theory permits to evaluate the effects of confinement on the ionic vapor – ionic liquid coexistence envelope. We have shown that due to confinement in pores with uncharged walls the critical temperature of the model decreases compared to the bulk. Also the coexistence envelope of the transition is narrower in comparison to the bulk model. The transition between dense and dilute phase represents capillary evaporation. We have analyzed changes of the density profiles of ions during transition. Possible extensions of this study are discussed.